O processo de ensino e aprendizagem da língua portuguesa para alunos surdos na Escola Enedina Sampaio Melo, Igarapé-Miri-PA - SILVA, Rosileno Pantoja da (2019)
The present research entitled The Teaching and learning process of the Portuguese language for deaf students of the Enedina Sampaio Melo School, Igarapé-Miri-PA, investigates the teaching and learning process of deaf students included in regular teaching classes at Enedina Sampaio Melo municipal school of Igarapé-Miri, especially in what concerns the Portuguese language. It seeks to understand the educational interfaces of these students, although they are inserted in regular classes of teaching. Therefore, the present research aims to constitute an opportune moment of knowledge and knowledge production about the understanding of the Portuguese language by the deaf students.